Potentiality of Taubah (Islamic repentance) and Listening to the Holy Quran Recitation on Galvanic Skin Response - Salam, Urme; Muhammad Nubli, Abdul Wahab; Ahmad, Ibrahim (Academic Journals, 2013)

(untitled)
Taubah and listening to the Holy Quran recitation are highly recognizable Islamic repentance to the Muslim community. Undoubtedly, these beliefs can flourish people's mind and soul. Therefore, this repentance has a miraculous power to reduce anxiety and stress like psychological pessimistic matters from one's mind. Besides this, listening to the Holy Quran recitation can relieve and calm a disturbed mind. Consequently, this repentance may be used as the therapeutic agents in some cases. In this work, the authors make use of taubah and listening to the Holy Quran recitation as stimuli in psychophysiological research, via galvanic skin response (GSR), an objective method for realizing the changes of emotional response of subjects. The results show that GSR can be used as a measure of mental states by listening to the Holy Quran. The effect of listening to the Holy Quran recitation on GSR is compared with that of taubah. Both taubah and listening to the Holy Quran recitation display changes on GSR; however the former reflects the greater changes than the latter.